Serbian Woman Defends „Woman Writer“: Apologetic Discourses in the Diary of Milica Stojadinović Srpkinja (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This paper analyzes various apologetic strategies used by Milica Stojadinović, the Serbian woman, in her diary entitled In Fruška Gora in 1854. The paper is focused on the defense discourses which aim at convincing the Serbian public that female authorship is not damaging but beneficial for the national struggle. By presenting herself as a sincere patriot and an exemplary Serbian woman, devoted not only to doing chores and other female duties, but also to writing poetry, reading mythological and philosophical books, translating European literature and collecting Serbian folk poetry and tales, Milica Stojadinović was trying to clear her reputation as an eccentric and false poetess, and to convince the Serbian people in the dignity and the importance of her role as the national poetess. The paper emphasizes her pleads for woman’s right to acquire a thorough education, to chose to become a woman writer, and to express herself in a creative way.
Keywords: diary; autobiography; defense discursive strategy; Milica Stojadinović; Serbian woman; Woman Writer